Trump digs votes: The effect of Trump's coal campaign on the presidential ballot in 2016 - Philipp Steinbrunner; Marina Di Giacomo; Wolfgang Nagl (Austrian Institute of Economic Research (WIFO), 2024)
In this paper, we investigate the effect of Donald Trump's campaign for coal during his successful race for the White House in 2016. We use a twofold empirical strategy. First, we estimate an event study model to show the change in Republican Party shares in coal counties in 2016 relative to other presidential election years. Then, we use a spatial Durbin Error model to estimate the impact of coal production on the Republicans' vote share in the US Presidential Election of 2016 at the county level. To avoid biased estimates, we consider spillover effects and employ spatial clustering. We find a sudden increase in the Republican Party's share of votes in coal counties in 2016, related to the pledge. When we account for the effect of the size of coal production, which differs across coal counties, as well as spillover effects, we again find a significant positive effect for coal counties. The result becomes even more pronounced when we use the vote-share difference between Mitt Romney in 2012 and Donald Trump in 2016 as the dependent variable. The positive effect of coal production on the Republicans' vote share remains significant after accounting for non-linear effects of coal production and using coal production per worker and per working hours as the main explanatory variables. Our results support the assertion that presidential campaigns significantly influence vote shares.
Keywords: D72; P16; P18; R11; 330; U.S. Presidential Election 2016; Coal Production; Durbin Model